Toronto’s Hippie Disease: End Days in the Yorkville Scene, August 1968 - Henderson, Stuart (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2006)
AbstractIn mid-summer, 1968, the idea that the hip Yorkville district represented a pox on the face of Toronto became a kind of reality: Hepatitis appeared to be taking over the scene. Throughout the 1960s, Yorkville had been framed as a neighborhood at risk, a symbolically “sick community” by its many detractors. It had been variously described as a “festering sore” and a “madhouse” by city fathers. But with an apparent Hepatitis epidemic came the opportunity to establish Yorkville as a new variety of illness. Yorkville was no longer figuratively sick, it was now quite literally infected. Throughout the month of August, 1968, Yorkville’s hip youth culture became the lepers of Toronto. Even though when by September all evidence showed that the Hepatitis rate in Yorkville was in no way indicative of an epidemic – all but two of the Villagers tested turned out to be intravenous drug users, signifying that the disease was being spread through dirty needles, not food or water – the damage was done, and Yorkville’s hip scene would never recover. Interrogating this pivotal episode in the Yorkville narrative, this paper explores the role of local media in the acceleration and dissemination of fears associated with a Hepatitis outbreak that, really, never was.